Malaria, blood glucose, and the role of tumour necrosis factor (TNF) in mice - ELASED, K M (Blackwell Science Inc, 1996)
Hypoglycaemia in falciparum malaria is associated with a poor prognosis and is correlated with mortality. High levels of serum TNF are also correlated with disease severity and mortality, and it has been suggested that TNF may cause the hypoglycaemia. However hypoglycaemia in mice infected with Plasmodium chabaudi or the lethal strain of P. yoelii YM is related to hyperinsulinaemia. Its development was not prevented by treatments which diminished TNF activity or production without affecting levels of plasma insulin. Conversely, it was inhibited by diazoxide, which inhibited insulin secretion but did not affect TNF production. Furthermore, in mice exhibiting neurological symptoms during infection with P. berghei, blood glucose concentrations were significantly raised when TNF levels were high, and TNF levels in the spleen were highest of all in non-lethal P. yoelii infections in which hypoglycaemia does not occur. Administration of human rTNF to normal animals caused an increase rather than a drop in blood glucose levels. Mice transgenic for human TNF did not develop hypoglycaemia when infected with P. yoelii YM, but showed signs of insulin resistance. In line with current views on the role of TNF in obesity and the control of glucose homeostasis, we conclude that the hypoglycaemia of malaria is not caused by increased levels of TNF, which may in fact be beneficial, but is secondary to a hyperinsulinaemia that is probably stimulated directly by products of the parasite.